2016
DOI: 10.1111/desc.12422
|View full text |Cite
|
Sign up to set email alerts
|

Comprehending text versus reading words in young readers with varying reading ability: distinct patterns of functional connectivity from common processing hubs

Abstract: Skilled reading depends on recognizing words efficiently in isolation (word-level processing; WL) and extracting meaning from text (discourse-level processing; DL); deficiencies in either result in poor reading. FMRI has revealed consistent overlapping networks in word and passage reading, as well as unique regions for DL processing, however less is known about how WL and DL processes interact. Here we examined functional connectivity from seed regions derived from where BOLD signal overlapped during word and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 82 publications
9
55
0
Order By: Relevance
“…Of neurological significance, many of the changes from time 1 to time 2 in mean fMRI connectivity involved angular gyrus, which has been shown to be involved in reading comprehension [1,50]. In addition, many of the functional connections in brain observed in the current study for reading tasks coincide with ones that have been identified in meta-analyses for handwriting [49] and word spelling [52].…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Of neurological significance, many of the changes from time 1 to time 2 in mean fMRI connectivity involved angular gyrus, which has been shown to be involved in reading comprehension [1,50]. In addition, many of the functional connections in brain observed in the current study for reading tasks coincide with ones that have been identified in meta-analyses for handwriting [49] and word spelling [52].…”
Section: Discussionsupporting
confidence: 52%
“…2. The seed point is known to be involved in reading [1,50]; and the region with which it is connected, the cingulate, is known to be involved in executive functions for written language [4,14]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Jülich histological (cyto-and myeloarchitectonic) atlas [12,13] is part of this software. Although the Jülich atlas contains many important language-related brain regions, it does not contain a specifically named region for the angular gyrus which is important for the functional reading brain [40]. However, the Jülich atlas does contain the inferior parietal lobule and its sub-parts which overlap with the angular gyrus.…”
Section: Data Analysesmentioning
confidence: 99%
“…In recent years functional magnetic resonance imaging (fMRI) studies have begun to reveal a network of regions that contributes to the construction of coherent mental representations of narratives (e.g., Egidi & Caramazza, 2013;Ferstl & Von Cramon, 2001;Mason & Just, 2006;Virtue, Haberman, Clacny, Parrish, & Beeman, 2006;Xu, Kemeny, Park, Frattali, & Braun, 2005;Yarkoni, Speer, & Zacks, 2008), as well as expository texts (e.g., Aboud, Bailey, Petrill, & Cutting, 2016;Moss & Schunn, 2015;Swett et al, 2013). In a comprehensive meta-analysis of neuroimaging studies on text comprehension processes, Ferstl, Neumann, Bogler, and von Cramon (2008) showed that this type of higher level language comprehension involves activation in many brain regions.…”
mentioning
confidence: 99%